Linkages between political brand image, affective commitment and electors loyalty: the moderating influence of reference group - Alkhawaldeh, Abdelbaset M.; Md Salleh, Salniza; Halim, Fairol (Asian Society of Business and Commerce Research, 2016)
The research in elector' loyalty to party brand was still fragmented, isolated and under research. This research aims to investigate the relationship between party brand image and elector loyalty to party brand, as well evaluate the mediation role of elector' affective commitment in primary relationship in line with social exchange theory and the role of the moderating influence of utilitarian reference group (tribe) in accordance with social comparison theory, to fill these gaps in marketing literature and to address the mixed findings in the previous studies.87 survey swere obtained from electors toward party brand in Jordan context using systematic random sampling method.The data were analyzed using SPSS and PLS-SEM techniques.Result shows that there is a positive relationship in direct and indirect paths, whereas, no support for the moderator hypothesis.Ultimately, the study introduced a number of recommendations and set of directions for future research.